Morphological, morphometric and histochemical aspects of the labial salivary glands of dogs - Galvão, Simone Rezende; Cunha, Daise Nunes Queiroz da; Del Carlo, Ricardo Junqueira; Borges, Andréa Pacheco Batista; Benjamin, Laércio dos Anjos; Fonseca, Cláudio César; Marcon, Lucas; Pereira, Carlos Eduardo Real (Semina: Ciências Agrárias, 2016)
The knowledge regarding labial salivary glands is becoming progressively more important, as their application in autologous transplantion, to promote ocular surface lubrication, are an ever-increasing procedure in veterinary medicine. In this study the labial salivary gland was collected, as a single piece, along with the oral mucosa from 10 adult dog cadavers. The sample was removed from the left lower lip marked by the second premolar tooth and extended until the distal edge of the second molar. Morphological, morphometric and histochemical evalutations were performed in the rostral, medial and caudal regions of the sample. The study revealed exocrine, compound, tubuloacinar, mixed and predominantly mucous glands with the presence of serous demilunes associated with a few mucous secreting units, and a duct system formed by intralobular intercalated and striated ducts, interlobular ducts, and a main excretory duct. In the rostral region, there was a lower amount of parenchyma compared to other areas, and the diameter of the acini unvaried in all regions. All three regions of the sample were PAS and Alcian blue positive, demonstrating the presence of neutral, carboxylated, and sulphated mucins. Serous demilunes reacted positively to Xylidine Ponceau staining indicating the presence of proteins.